К вопросу определения нагрузочных режимов блокируемых и самоблокирующихся межколесных дифференциалов военных колесных машин - Волонцевич, Дмитрий Олегович; Мормило, Яков Михайлович (НТУ "ХПИ", 2017)
Проведен анализ необходимой величины коэффициента блокировки межколесного дифференциала для получения максимальной силы тяги машины по сцеплению в зависимости от возможного сочетания коэффициентов сцепления под бортами. Обоснован переход от коэффициента блокировки к блокировочному моменту дифференциала для машин, рассчитанных на движение при возможном полном вывешивании одного или нескольких колес. Предлагается алгоритм построения зависимости необходимого блокировочного момента межколесного дифференциала от частоты относительного вращения полуоси и корпуса дифференциала на примере колесного бронетранспортера БТР-4.

The analysis of existing technical solutions for lockable and self-locking differentials wheeled vehicles intended for off-road. Were evaluated the required value of lock ratio of cross-axle differential for maximum traction force of the machine depending on the possible combinations of coefficients of adhesion under the wheels. Substantiated transition from lock ratio to the locking torque of differential for machines designed for movement with the possible full hanging one or more wheels. An algorithm for plotting the necessary locking torque of cross-axle differential from the frequency the relative rotation of axis and the differential case on the example of a wheeled armored personnel carrier BTR-4 is proposed. This could be relevant for the development of an electronic system of automatic control lock ratio and for generating performance requirements of gerotor differential.
To the question of determining the load mode of blockable and self-blockable cross-axle differentials of military wheeled vehicles
Keywords: бронетранспортер; трансмиссия; проходимость; коэффициент блокировки; armored personnel carrier; transmission; passability; lock ratio